2019
DOI: 10.1159/000496111
|View full text |Cite
|
Sign up to set email alerts
|

DNA Methylation of the Leptin Gene Promoter is Altered by Chronic Alcohol Exposure in an Animal Model for Alcohol Dependence

Abstract: Appetite-regulating peptides, such as leptin, are linked to craving and have been in the focus of alcohol dependence research for years. The objective of our study was to investigate the dynamics of leptin gene promoter methylation during alcohol withdrawal and specific treatment in a rodent (rat) model for alcohol dependence. DNA methylation was measured using direct bisulfite sequencing at 0 h, 24 h, and 6 days of alcohol withdrawal as well as after treatment with alpha-melanocyte-stimulating hormone (alpha-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…It has been revealed a notable reduction in DNA methylation levels in the leptin promoter region of animals consuming alcohol compared to those who had not been exposed to alcohol. However, after a period of 6 days without alcohol consumption, this disparity in methylation levels ceased to exist [50]. Adolescent intermittent ethanol (AIE) exposure has been found to cause significant alterations in DNA methylation mechanisms within the amygdaloid circuitry.…”
Section: Animal Studiesmentioning
confidence: 99%
“…It has been revealed a notable reduction in DNA methylation levels in the leptin promoter region of animals consuming alcohol compared to those who had not been exposed to alcohol. However, after a period of 6 days without alcohol consumption, this disparity in methylation levels ceased to exist [50]. Adolescent intermittent ethanol (AIE) exposure has been found to cause significant alterations in DNA methylation mechanisms within the amygdaloid circuitry.…”
Section: Animal Studiesmentioning
confidence: 99%
“…In addition to the heterogeneity in outcomes seen, studies have also suggested that methylation levels in some regions due to alcohol cease to exist after a particular period making understanding the duration of these changes important (Wieting et al, 2019). Nevertheless, as we have demonstrated, the effects of PPAC can occur in offspring born to sires who were not exposed to alcohol for 8 weeks before mating and the next step is to identify the changes which support epigenetic inheritance through the male germline.…”
Section: Mechanisms Of Ppacmentioning
confidence: 84%